2021
DOI: 10.52747/aqujie.1.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Does Usage of Islamic Microfinance Products Influence the Income, Education, and Health in Mauritania?

Abstract: This paper attempts to determine the effect of the use of Islamic microfinance (IsMF) products on Mauritanians' income, education, and healthcare, as well as the gender invariance in the model. The article uses cross-sectional design data gathered through a questionnaire from a sample of 381 beneficiaries of the largest IsMF institution in Mauritania, PROCAPEC-Nouakchott. Using the Structural Equation Modeling (SEM) method, the results found that the use of IsMF products has a significant impact on the income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…According to Maouloud et al. (2021), Islamic microfinance products such as Murabahah , Qard al-Hasan and savings have a positive impact on microenterprise development, leading to increased household income levels.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Maouloud et al. (2021), Islamic microfinance products such as Murabahah , Qard al-Hasan and savings have a positive impact on microenterprise development, leading to increased household income levels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Naveed Aslam (2014) investigated the role of microfinance in reducing poverty in Pakistan, concluding that the living standards of clients improved because of the Islamic microfinance program, which also played a significant role in increasing per capita income, educational level and employment in Pakistan. Furthermore, a study carried out in Tunisia demonstrated that the economic empowerment of beneficiaries was achieved through the availability of Islamic microfinance(Zitouni and Jedidia, 2022).According toMaouloud et al (2021), Islamic microfinance products such as Murabahah, Qard al-Hasan and savings have a positive impact on microenterprise development, leading to increased household income levels. Equity financing of Islamic microfinance products through Musharakah and Mudarabah can further enhance beneficiary income and expenditure while alleviating poverty…”
mentioning
confidence: 99%